Peningkatan Hasil Belajar Bola Voli Melalui Pembelajaran Project Based Learning pada Peserta Didik Kelas IV SDN Babatan IV Surabaya - Dista Nur Aini; Nanik Indahwati; Christof Advanta Taringan (Journal of Creative Student Research, 2024)
Low achievement of students in basic passing techniques in big ball games such as volleyball. The percentage of completeness of learning outcomes has not reached the Minimum Completeness standard (KKM), with many students not completing this learning. This research seeks to increase the quality of learning outcomes, knowledge, skills and other aspects to improve learning for students. This research uses classroom action research techniques. This technique is to collect data related to the research object with the main aim of overcoming the problems that occur. This research was conducted at SDN Babatan IV Surabaya involving 25 students, including 10 boys and 15 girls. This research process involves the following steps: planning, implementing actions, observing or evaluating, and reflecting. The results of research involving 25 class IV students at SDN Babatan IV Surabaya, showed a significant increase from cycle I to cycle II. In cycle I, only 12% of students achieved completeness, while in cycle II, there was a drastic increase to 80%, an increase reaching 68% through the STEAM-based PJBL learning method, which supports students to understand the material better.